Percolation Evolution and Characteristics in the Formation Process of Pores for Porous Graphite - Wang, Qili; He, Min; He, Yaqun; Hu, Yafei; Liu, Qi (Asian Journal of Chemistry, 2014)
The micro-pore structure and distribution of graphite during the forming process of pores in roasting is developed and the evolution process from a local connection to infinite connectivity of pores is analyzed by percolation theory. The percolation characteristics of micro-structural images are analyzed based on the renormalization group method and the micro-pore structure is measured by mercury injection test. The analysis and experimental results show that the nature of the forming process of pores in roasting is the percolation evolution process from local area and finite clusters to global material and infinite clusters.The area porosity of graphite samples for filtration ranges from 0.541 to 0.588 and the volume porosity ranges from 0.297 to 0.403, which are greater than the threshold and have percolation structure. On the other hand, the area porosity of graphite samples for impregnation ranges from 0.189 to 0.314 and the volume porosity ranges from 0.107 to 0.155, which are smaller than the threshold and have no percolation structure.